La méthode de l’évaluation des risques sanitaires en France : représentations, évolutions et lectures plurielles - Franck Boutaric (VertigO)
Sanitary risk assessment methodology in France: representations, mutations, and plurality of interpretationsAmong the scientific methodologies whose destiny accompanies the constancy and mutations in the expertise of French society, sanitary risk assessment has had success. For nearly fifteen years, this tool has seen its design and connections with risk management undergo a certain number of modifications. Representations and interpretations differ whether the administrative, political or scientific field pounce on them. This flexibility is due to the developments of scientific research and to the disciplinary perspectives contributing to the elaboration of sanitary assessment. It not only refers to how the methodology is used but also to the changing patterns of sanitary security impacting both understanding and practice. Despite the determination to integrate the stakeholders in the evaluation process, these transformations, whose current status and future prospects remain uncertain, are still the work of forces seldom acting outside institutional structures.